A Little Princess - Burnett, Frances Hodgson, 1849-1924 (Lahore Readings Publishing, 2016)
Follow the fortunes of Sara Crewe as she goes from riches, to rags, to riches again, in this heart-warming classic tale of hardship, hope, and of finding friendship in the most unlikely places
Keywords: Orphans -- England--London -- Schools